Microleakage of cervical cavities prepared by an Er:YAG laser or a high-speed handpiece, after restoration using resin composite - Daneshkazemi, Alireza; Bahrololoomi, Zahra; Davari, Abdolrahim; Omidi, Arash; Daneshkazemi, Pedram (Journal of Dental School, 2019)
Objectives The purpose of this in vitro study was to evaluate the microleakage of cervical cavities prepared by Er:YAG laser or high-speed hand piece and bur. Methods This in vitro experimental study was performed on 40 sound permanent third molar teeth randomly assigned into two equal groups (n = 20). In the first group, high-speed hand piece and bur and in the second group Er:YAG laser was used to prepare class V cavities on the buccal or lingual surfaces. Filtek Z250 composite resin was used as the restorative material. The teeth were thermocycled for 1000 cycles, placed in 2% methylene blue solution for 24 hours, sectioned at the center of restoration and evaluated under a stereomicroscope at x40 magnification for microleakage. Data were analyzed using Mann-Whitney U test at 0.05 level of significance. Results There was no significant difference between the occlusal or gingival margin microleakage of cavities prepared with Er:YAG laser and high-speed hand piece (P = 0.445 and P = 0.758, respectively). However, the difference in the occlusal and gingival margins was significant within the high-speed hand piece (P = 0.042) and Er:YAG laser (P = 0.002) groups. Conclusion Cavity preparation by Er:YAG laser and high speed hand piece and bur is not significantly different in terms of microleakage.